Reynolds Privilege Defence In Malaysia: The Aftermath Of Dr Syed Azman Syed Ahmad Nawawi & Ors v. Dato’ Seri Hj Ahmad Said [2015] 7 CLJ 180 And Syarikat Bekalan Air Selangor Sdn Bhd v. Tony Pua Kiam Wee [2015] 8 CLJ 477:Part 2 - Sardar Baig, Farheen Baig; Ali Mohamed, Ashgar Ali (2018)
This article follows from part 1 in which some observations were made by the authors on the Reynolds privilege defence and how it differed from the defence of qualified privilege. In part 1, the confusion that arose from a wrong plea of defences was extracted and brought to light. To continue in this article, the authors submit that the confusion had surfaced with variations of the defences pleaded, pre and post-Dr Syed Azman and Syarikat Bekalan. Below are the cases that followed after the landmark case of Reynolds v. Times Newspaper that had propounded the Reynolds privilege defence. The purpose of the table is to show how the defence was pleaded in cases where an action for defamation arose due to widespread publication of disparaging words.